Throughput Performance of 4G-based UAV in a Sub-Urban Environment in Malaysia - Mohd Kamal N.L.; Sahwee Z.; Norhashim N.; Lott N.; Abdul Hamid S.; Hashim W. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cellular radio systems; Mobile telecommunication systems; Unmanned aerial vehicles (UAV); Urban planning; Wireless networks; Cellular network; Malaysia; Real measurements; Received signal strength; Throughput performance; Urban environments; Antennas